Postal Operations and Environmental Protection - Nada Štrumberger; Stjepan Paler; Saša Šolman (Promet - Traffic&Transportation, 1970)
Increased awareness of the problems related to environmentalprotection and numerous activities undertaken in thisfield represent one of the basic characteristics of the present.The Universal Postal Union - UPU, has also become aware ofthe threat to our environment and the need for urgent measuresin environmental protection. Not only do they understand theneed to act, but are also aware that they have the possibility ofsignificantly contributing to the preservation of the environment.The paper presents the activities that UPU has undertakenor is undertaking with the aim of reducing the environmentalpollution, as well as some practical experiences of thedeveloped postal administrations in applying the system of environmentalprotection management in the postal technologicalprocesses.